Factors Associated with Sexual Victimization Among Transgender Emerging Adults - Tubman, Jonathan G. (Journal of interpersonal violence, 2024)
This cross-sectional study documented between-group differences in risk factors associated with sexual victimization histories in an ethnically and racially diverse sample of transgender emerging adults (N = 248, ageM = 22.61 years). The sample was recruited using the Internet-based CloudResearch platform to answer questionnaires assessing predictors for recent experiences of intimate partner violence (IPV). Participants were categorized into four groups based on cross-classified self-reports of child sexual abuse (CSA) and recent sexual IPV, prior to the use of multivariate analysis of variance to evaluate mean score differences for past-year substance use, minority stressor, and relationship functioning variables. Participants reporting sexual IPV reported higher scores for all substance use variables, while transfeminine participants reported significantly higher scores for alcohol use problems and negative consequences related to substance use. Participants reporting both CSA and sexual IPV also reported the highest scores for everyday discrimination. Participants who experienced sexual IPV also reported the highest scores for internalized sexual stigma. Sexual revictimization among transgender adults occurs in the context of harmful patterns of substance use and several minority stressors. Our findings have implications for healthcare or counseling services for transgender emerging adults who have experienced multiple forms of victimization, substance use problems, and minority stressors, including the importance of trauma-informed and integrated intervention services, and specialized training for service providers.